Treino remoto parental para aplicação do protocolo de avaliação do ecoico a crianças com autismo - Galego, Pâmela Suelen (2022)
Autism Spectrum Disorder (ASD), among its defined characteristics, is the deficit in social communication, one of the factors of greatest concern for parents. Teaching how to develop this skill in your child, in addition to extending the intervention time, is a treatment with satisfactory results. The verbal response is a behavior mediated by a listener, that is, the behavior responds to verbal stimuli and by contingency, based on the contingency between the stimuli that precede and follow the emission of the verbal control. The main verbal operants described in the literature are: mand, tact, echoic, intraverbal, textual and copy. The importance of teaching echoic in the child's development is highlighted, as it is a prerequisite for the installation of other more complex verbal behaviors, in addition to providing the learning of social skills. With regard to the scenario of social isolation, an intervention is made to the mental health of children at risk, especially the probability of risk and, at the same time, to a work group and efficiency of operations. The Behavior Skills Training package was useful to teach parents how to use behavioral procedures with their children with ASD in the home environment. The present study aimed to use caregivers/parents to use the generalized echoic repertoire assessment protocol with autism via remote video-modeling training. Through a multiple baseline design, the results of five participating mothers were observed. The results indicate the diligence of the teaching procedure. For two mothers, their exposure to video modeling was not indicated, given as instructions was sufficient for their video modeling presentation. Video modeling accelerates the learning process.